Books vs. Journal Articles: a Diachronic Study of Referencing in Written Medical English Prose (1810-1995) - Salager–Meyer, Françoise (The ESPecialist, 2012)
The objective of the present paper is to examine the qualitative and quantitative diachronic evolution of references made to books and journal articles and that of their linguistic origin over a 185 year-period. We analyzed a corpus of 162 medical articles published in 34 different British and American medical journals between 1810 and 1995. The results obtained were grouped according to the 4 distinct year-blocks identified in our previous study (Salager-Meyer, 1996a). Between-block comparisons were performed by means of Chi-square tests. Our global results showed that: a) English-written (E) sources were more frequently cited than sources written in other languages (NE); b) journal articles were also more frequently referred to than books, and c) E journals were more frequently cited than NE journals. The quantitative and qualitative differences put forward by our data are analyzed and discussed within a social-constructivist perspective. The diachronic evolution observed over the 185 years studied reflects how the birth and growth of medical specialties and sub-specialties have influenced referencing behavior as well as the changing role journals and books have played over time as knowledge sources.